Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1046/j.1464-410x.1998.00828.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of a collagen sponge for engineering urothelial grafts

Abstract: Objective To investigate the deposition of urinary crys-Results No crystals were evident on any of the collagen sponges. Calcium deposition was negligible at pH 5.3. tals and the growth characteristics of urothelial cells on a collagen sponge, as a preliminary step in enginAlthough calcium levels were measurable at pH 6.3, the levels were very low. Both cell lines attached and eering urothelial autologous grafts. Materials and methods Collagen sponges were exposed grew in a stratified manner on the collagen sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 30 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…The epithelium on vein graft was confirmed by IHC using pancytokeratin antibody. Pancytokeratin has been found to be a useful marker for the identification of urothelium [29] .…”
Section: Discussionmentioning
confidence: 99%
“…The epithelium on vein graft was confirmed by IHC using pancytokeratin antibody. Pancytokeratin has been found to be a useful marker for the identification of urothelium [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts grow for 7 weeks on dermal collagen preparations from pigs, forming confluent layers with migration of cells into the matrix [12] . Sabbagh et al [13] seeded urothelial cells on collagen films and observed multiple cell layers with a maximal cell proliferation between 5 and 10 days. Further supporting factors of cell growth on collagen scaffolds are growth factor such as epidermal growth factor [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Collagen-GAG sponges were used in the present study because variants of these sponges are now widely adapted as clinically useful forms of dermal substitute (produced commercially as Integra TM ) or as tissue engineering cell supports. [40][41][42] These are relatively dense, stable, and mechanically stiff, porous matrices, containing small amounts of the GAG chondroitin sulfate. 43,44 They have previously been shown to support fibroblast force generation in three-dimensional culture, 15,45 and are claimed to reduce contraction clinically, making them good candidate cell substrates to study in this model.…”
mentioning
confidence: 99%